INTS7–ABCD3 Interaction Stimulates the Proliferation and Osteoblastic Differentiation of Mouse Bone Marrow Mesenchymal Stem Cells by Suppressing Oxidative Stress - Liu, Yubo; Yu, Xiao; Huang, Anquan; Zhang, Xiangxin; Wang, Yijun; Geng, Wei; Xu, Renjie; Li, Suoyuan; He, Hui; Zheng, Bo; Chen, Guangxiang; Xu, Yaozeng (Frontiers in Physiology, 2021)
Increased adipocyte and decreased osteoblast differentiation, combined with the ectopic proliferation of bone marrow mesenchymal stem cells (BM-MSCs), represent the primary causes of osteoporosis. The dysregulation of numerous intracellular bioactive factors is responsible for the aberrant differentiation and growth of BM-MSCs. In this study, we focused on a new stimulative factor, integrator complex subunit 7 (INTS7), and its cooperative protein ATP-binding cassette subfamily D member 3(ABCD3)/high-density lipoprotein-binding protein (HDLBP) in mouse BM-MSCs. We aimed to uncover the effects of the INTS7–ABCD3/HDLBP interaction on BM-MSC biological behaviors and the potential mechanism underlying these effects. Functional in vitro experiments showed that the suppression of the INTS7–ABCD3 interaction rather than HDLBP could impair BM-MSC proliferation and induce cell apoptosis. Moreover, Alizarin Red S and Oil Red O staining, respectively, revealed that INTS7 and ABCD3 knockdown but not HDLBP knockdown could decrease osteoblastic differentiation and accelerate the adipogenic differentiation of BM-MSCs. Mechanistically, reactive oxygen species (ROS) and histone γ-H2AX quantities significantly increased, whereas the levels of antioxidants declined due to INTS7 and ABCD3 inhibition in BM-MSCs. These findings indicated that the suppression of oxidative stress could be involved in the INTS7/ABCD3 co-regulatory mechanisms for BM-MSC proliferation and differentiation, identifying new potential candidates for osteoporosis therapy.